Перспективи створення та функціонування кооперативних банків в Україні - Сембер, С.В.; Брітченко, І.Г.; Стойка, В.С. (Економіка промисловості, 2017)
Розглянуто досвід провідних країн Європи щодо побудови системи даних фінансових інститутів та їх значення для економічного розвитку. Обґрунтовано доцільність створення кооперативних банків на території нашої держави. Акцентовано увагу на проблемах законодавчого та організаційного характеру щодо функціонування таких банківських установ в Україні. Рассмотрен опыт ведущих стран Европы относительно построения системы данных финансовых институтов и их значение для экономического развития. Обоснована возможность создания кооперативных банков на территории нашей страны. Акцентировано внимание на проблемах законодательного и организационного характера по поводу функционирования таких банковских учреждений в Украине. The article is devoted to the prospects of creation and functioning of cooperative banks in Ukraine. The experience of leading countries in Europe regarding building the data systems of financial institutions and their importance for economic development have been considered. The article deals with the peculiarities of development and operation of the cooperative banks of developed countries: Germany, France, Italy, Austria, Netherlands, and Poland. The specific character of the functioning of these banking institutions and their place within the banking system of the corresponding countries has been determined. The article focuses on the cooperative banks in Germany that is the homeland of the credit cooperation in Europe. Traditional operations of the cooperative banks of the above mentioned country as well as their charitable activity have been described. The tendency to the merging of the regional cooperative banks of Germany is of a special interest. Owing to this fact the cooperative system of the country has acquired current power and financial strength. The functioning of Austrian banking group “Raiffeisen” that is the biggest cooperative banking group of Austria has been analyzed. An accent is made on the development of the system of cooperative banks of Italy that includes two groups - Banche Popolari і Banche di Credito Cooperativo. The authors emphasize the key role of cooperative banks for the development of the agrarian sector of such countries as France and the Netherlands.On the basis of the study of the experience of developed European countries concerning the formation of cooperative banking sector the main lines of development of cooperative banks in Ukraine have been suggested. The expediency of creation of cooperative banks in our country has been substantiated. The attention is focused on the problems of legislative and organizational nature regarding the operation of such financial institutions in Ukraine. A three-tier model of national cooperative bank system has been suggested. It should be based on a "bottom-up" principle and consist of three levels, each of which must perform the relevant function. The first level of credit cooperative system should be represented by local cooperative banks. The second level should be formed by regional cooperative banks. At the third, national level, should be the central cooperative bank, which logically completes the construction of a full-fledged cooperative system. The result of the activity of these institutions should be a rational financing of small businesses and a rapid response to their needs, as well as the reduction of loan costs to farmers and the promotion of agriculture in general.